PERBANDINGAN KINERJA PEMERINTAH DAERAH DI INDONESIA - Netty Nurhayati; Fahmi Rizani; Kadir - (Universitas Trunojoyo Madura, 2019)
This study aims to compare the performance of district / city governments in Indonesia that obtain WTP and Non-WTP opinion from BPK RI for 2014-2016 period. The financial performance variables are measured by financial ratios (decentralization degree ratio, independence ratio, effectiveness ratio , growth ratio) and performance of local government administration are measured by performance evaluation score of local government administration (EKPPD score). Sampling method using purposive sampling with judgment sampling technique. The sample in this study 216 districts / cities, consisting of 108 districts / cities that obtain WTP opinion and 108 districts / cities that obtain Non-WTP opinion. Hypothesis testing using nonparametric test ‘Mann-Whitney U Test’. The results of this study, state that the financial performance of local government and performance of local government administration on district / city governments in Indonesia that obtain WTP opinion is significantly different and better than district / city governments in Indonesia that obtained Non-WTP opinion. This difference shows that district / city government that obtain WTP opinion has proven to be better in terms of financial management and local government administration compared to those who obtain Non WTP opinions.